Transanal submucosal polyacrylamide gel injection treatment of anal incontinence: a randomized controlled trial. (14th March 2016) - Altman, Daniel; Hjern, Fredrik; Zetterström, Jan
Abstract: Introduction: The efficacious and safe use of transurethral injections of polyacrylamide hydrogel (Bulkamid ® ) in women with stress urinary incontinence suggests that it may be suitable also for treatment of anal incontinence. We aimed to determine the effectiveness and safety of polyacrylamide hydrogel when used as a transanal submucosal bulking agent in women with anal incontinence. Materials and methods: Thirty women with a diagnosis of anal incontinence and a Cleveland Clinic Incontinence Score (CCIS) >10 were randomized to three different techniques of transanal submucosal injections using polyacrylamide hydrogel. Follow up was performed at 2, 6 and 12 months using CCIS and the Fecal Incontinence Quality of Life scale (FIQL). Results: In all, 29 of the 30 women completed the follow up. Approximately half of the women requested a re‐injection at the 6‐month visit. The overall CCIS improved significantly from baseline (14.7. SD 2.5) to 1 year (12.4. SD 3.1) ( p = 0.003). There was a significant improvement with regard to the occurrence of loose fecal incontinence ( p = 0.014) but not for solid fecal incontinence ( p = 0.28). At 1 year the FIQL domains of coping‐behavior, depression, and embarrassment showed significant improvements ( p = 0.012, p = 0.007 and p = 0.007, respectively). We recorded no adverse events related either to the injection technique or the biomaterial. There were no significant differences between the treatment groups in either CCIS or FIQL scores. Conclusion: Transanal submucosal injection of polyacrylamide hydrogel resulted in a modest although significant overall improvement in anal incontinence symptom scores with corresponding improvements in several domains of quality of life, regardless of injection volume.